Manajemen Program Kegiatan Religius dalam Pembinaan Kecerdasan Spiritual Siswa di MA Miftahul Huda Cendono - Sofiyatin Nisa’; Ashari Ashari (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
The results of this study indicate that 1) The management of the religious activity program implements four management functions in fostering students' spiritual intelligence. It is proven by the implementation of management functions, starting from planning which includes determining the goals, activities, methods and coordination of teachers, implementation in the form of mentoring teachers in each activity, direct supervision and observation by the head of madrasah and teachers, finally evaluation of the programs that have been run. 2) The head of the madrasa in carrying out the program of religious activities implements methods of habituation, example, coaching and nurturing as well as methods of punishment and reward. From these management and efforts, this religious activity program has a positive impact on students, especially regarding morals. This extraordinary change in student behavior is due to the habituation of religious activities in the madrasa so that students' spiritual intelligence is formed.